Diseño de un plan de negocio de regenerado de aceite lubricante sintético en Bogotá (2020)
The companies situated on the lubricants industry, at the present time must be give relevance to the guidelines that are related to the quality; since in this way they protect the environment, reducing situations of leaks, spills and fires. By identifying industrial risk, corrective actions must be definite to mitigate spills of hydrocarbons and their derivatives on the field, also harmful substances in ocean and river waters. We need to consider the risk by analyzing accidents and incidents to create a model of contingency plan, specifically will be drawn up to the city of Bogotá, where corporate collaboration is raised. In this case, the approach on evaluation, organization and coordination will be focus on the recollection of synthetic oil used.